If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P(p + 1) = 132 Reorder the terms: P(1 + p) = 132 (1 * P + p * P) = 132 (1P + pP) = 132 Solving 1P + pP = 132 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Reorder the terms: -132 + 1P + pP = 132 + -132 Combine like terms: 132 + -132 = 0 -132 + 1P + pP = 0 The solution to this equation could not be determined.
| P(p+1)=12 | | [7(m+5)-15]+[3(m-2)+2]= | | H=16t^2+75t+4 | | X^5y^4/3xy/1/x^3y | | x+71+x+92=89 | | X^2-9/x-3=5 | | 6sin^2(x)-sin(X)-1=0 | | 5p+7=12+3p | | 186=2x | | X(5x+8)(7x-3)=0 | | -36x=-720 | | -70x=-560 | | 126=x+92 | | 2+6x=2+4x | | 26x=-78 | | -32x=96 | | -3x=108 | | -48x=96 | | -26x=104 | | c^2=-2c+45 | | x^2+2ax+a^2-9=0 | | -x=397 | | 41-7x=160 | | c^2=2c+16 | | 4(3x-1)=6(x-1) | | 23+x=19+11 | | 4x+3.75=x-6 | | Y=7/17 | | 11.3y=4052 | | (2y-5x-4)-(x-6y+5)= | | 38-4=8 | | 8(x)+10=-9 |